2002
DOI: 10.1152/ajpheart.00839.2000
|View full text |Cite
|
Sign up to set email alerts
|

AT1 and AT2 receptor expression and blockade after acute ischemia-reperfusion in isolated working rat hearts

Abstract: . AT 1 and AT2 receptor expression and blockade after acute ischemia-reperfusion in isolated working rat hearts. Am J Physiol Heart Circ Physiol 282: H1206-H1215, 2002; 10.1152/ajpheart.00839.2000.-We assessed ANG II type 1 (AT 1) and type 2 (AT2) receptor (R) expression and functional recovery after ischemia-reperfusion with or without AT1R/AT2R blockade in isolated working rat hearts. Groups of six hearts were subjected to global ischemia (30 min) followed by reperfusion (30 min) and exposed to no drug and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
1
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 42 publications
10
31
1
4
Order By: Relevance
“…Ang II elicits coronary vasoconstriction by activation of postsynaptic AT1R as well as presynaptic AT1R inducing catecholamine release that could exacerbate ischemic injury. Cardiac AT1R gene expression increased after IR in our experimental conditions, contrary to Xu et al (2002) who observed a decrease in AT1R mRNA, but consistent with other observations of cardiac AT1R induction in IR (Sun and Weber, 1994;Yang et al, 1997). The induction of AT1R may contribute to the increase in coronary vascular resistance and cardiac dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…Ang II elicits coronary vasoconstriction by activation of postsynaptic AT1R as well as presynaptic AT1R inducing catecholamine release that could exacerbate ischemic injury. Cardiac AT1R gene expression increased after IR in our experimental conditions, contrary to Xu et al (2002) who observed a decrease in AT1R mRNA, but consistent with other observations of cardiac AT1R induction in IR (Sun and Weber, 1994;Yang et al, 1997). The induction of AT1R may contribute to the increase in coronary vascular resistance and cardiac dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we observed a higher expression of AT 2 receptors after ACE inhibition, however, no difference in AT1 receptor expression. Whereas different studies have shown that Ang II down-regulates its own receptors (Iwai et al, 1991;Iwai and Inagami, 1992), there are conflicting reports about the regulation of the AT1 and AT2 receptors after ACE inhibition (Ouali et al, 1997;Zhu et al, 1999;Xu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, Ang II causes vascular injury and organ damage. In fact, several lines of evidence have implicated that inhibition of Ang II may protect against ischemia-reperfusion-induced tissue injury in the heart, brain, liver, kidney, and small intestine (1,5,17,42). Previous studies have shown that the increase in Ang II is more prominent in the splanchnic circulation than in the systemic circulation during major aortic surgery and hypovolemia (44).…”
Section: Discussionmentioning
confidence: 99%